(NkULXTURA WOKALXNOGO SLOWAs (NmETODIKAs - (Na(B.(Ni(B.(NkANKAROWI^s ((NmOSKWAs (NgOSUDARSTWENNOE MUZYKALXNOE IZDATELXSTWOs, 1957)
(Nw RABOTE a(B.(Ni(B.(NkANKAROWI^A O KULXTURE I MASTERSTWEs
Keywords: (NmETODIKAs